¿Es la depreciación suficiente? Liberalización externa en Brasil y lecciones para Ecuador - Vernengo , Matias (2001)
Just after Plan Real of Suly 1994 was performed, Brazil adopted the Washington Consensus creed of liberalization, deregulation, and privatization. At the carly nineties, the peculiarity in Brazil's reform process was the co-existence of capital and commerce liberalization along with high inflation. In an economic performance evaluation il is difficult to deny the fact that the nineties were for this country the true second lost decade. This document evaluates the consequences of reforms on macroeconomic performance, growth, labor, wage differentials, and income distribution in Brazil. And, the most relevant conclusion could be that what really matters is not the difference between inward or outward development strategtes, but the difference between open or closed financial regimes. It could be suegested on thc basis of this experience that if Ecuador intends to grow at rates higher that thc ones performed during the nineties without falling into current account unsustainable deficits, the liberalization process must be revised.